Aplicação do modelo matemático de Streeter-Phelps na análise de concessão de outorga de lançamento de efluentes em rios naturais - Lima, Eveline Vale de Andrade (2011)
Water is a natural resource that has been used in different sectors of human activity. However, often this diversity of use has generated conflicts of users, or environmental impacts. To try to regulate these uses and reduce these conflicts, especially in sparse areas such as the semi-arid regions, the National Water Resources Plan was approved, which is basically Management Instrument these natural resources. In this context, the granting of authorization for use of water bodies is one of those instruments covered in this plan and proposing legal bases for disciplining these uses. This work deals with the study of the development of a methodology, based on the Streeter-Phelps model to analyze the relevant relationships between the flow of a natural river and its ability to receive pollution loads, depending on a quality framework of its waters provided for each type of use. Considering the characteristics of the model used, were taken with reference to analysis, Demand concentrations Biochemical Oxygen (DBO) present in the effluents, as well as the concentrations of dissolved oxygen (DO) present in the river under study. The results show that to achieve optimal conditions for special class rivers, in semi-arid regions, such as Northeast Brazil, no need for a pretreatment to release, so that severe impact may be avoided.